Familial transmission of hepatitis B: an interesting case report - Debnath, Partha; Chavan, Vijay; Rane, Siddhesh; Jain, Shubham; Thanage, Ravi; Chandnani, Sanjay; Shankarkumar, Aruna; Rathi, Pravin M. (International Journal Of Community Medicine And Public Health, 2020)
Hepatitis-B is a health problem of global importance. India falls in the low intermediate endemicity zone (prevalence rate 2-4%) for hepatitis-B virus infection. Intrafamilial transmission of HBV has an important role in maintaining endemicity in our country. Here we report an interesting case of intrafamilial clustering of HBV infection from western India. Out of 14 family members, 12 members (85.7%) were hepatitis-B infected (overt or occult). This report highlights that vertical transmission of hepatitis-B is also an important route of hepatitis-B transmission. Screening of family members and contacts of HBsAg positive individuals with both HBsAg and Anti-HBc is required for timely active immunization and adaptation of hygienic precautions to prevent the chain of transmission of hepatitis B.